THE EFFECT OF FLIPPED CLASSROOM STRATEGY TOWARD STUDENTS READING COMPETENCE IN THE ENGLISH FOR NURSING - Suryati Ni Wayan Novi; Susandi Ni Kadek Ary; Susanta I Putu Agus Endra (Lingua Scientia, 2019)
This study aimed to identify the effect of flipped classroom strategy toward reading competence between students who are taught using flipped classroom and those who are taught using conventional strategy. The study employed quasi experimental and used Non-equivalent Control Group Design. There were 80 respondents of the 3rd semester nursing students of STIKES Bali recruited as the sample through purposive sampling strategy. The data were collected by using pre-test and post-test to measure students' reading competence. The findings indicated that there was a significant difference between experimental and conventional group. The average score of experimental group in pre-test was 49.05, while the post-test was 78.58; the increase was 29.53. Meanwhile, the average score of control group in the pre-test was 45.55, while after the post-test was 58.48; the increase was 12.93. The t test obtained the value of t count 12.737. The value of t table with df 39 at a significant level of 5% was 2.0226. Therefore, t count> t table (12,737> 2,0226) and the significance value is lower than 0,05 (0,00 <0,05). The students taught using Flipped Classroom achieved better in reading competency than those who were taught using conventional teaching. In conclusion, Flipped Classroom is an active learning strategy that can be applied in the classroom, in which the learning process is reversed, that is, from the student to the teacher or student-centered learning.